Effect of Different Surface Treatments and Application Times on Shear Bond Strength Between Polyetheretherketone and Composite Resin - Ozdogan, Alper; Topdagi, Basak (UI Scholars Hub, 2022)
Objective: To investigate the effect of various surface treatments and different application times on shear bond strength between polyetheretherketone and composite resin. Methods: A total of 110 disc-shaped polyetheretherketone specimens were randomly divided into 9 groups and 4 different surface treatments (control, sandblasting, tribochemical silica coating, sulfuric acid) were applied. The sandblasting, tribochemical silica coating, and sulfuric acid processes were performed 3 different times (10s, 15s, 20s). Then, the composite resins were applied to the treated surfaces of the polyetheretherketone specimens. The shear bond strength test and scanning electron microscopy analysis were performed. The data were statistically analyzed using analysis of variance and Duncan honest significant difference test. Results: One-way analysis of variance revealed differences in shear bond strength among the groups (p <0.001). While the control group showed the lowest bond strength values (4.24 ± 1.53 MPa), 20 s of sulfuric acid process showed the highest bond strength values (27.91 ± 4.44 MPa). Conclusion: Depending on the application time to the material, additional surface treatments increase the polyetheretherketone composite bonding. Surface treatments with sulfuric acid applications provide higher surface bonding values than other treatments.